Mengembangkan Bakat Kemandirian Murid Melalui Penerapan Strategi Outdoor Learning Dan Indoor Learning Pada TK Pertiwi Pompanua Kabupaten Bone - rosnah rosnah (Universitas Negeri Makassar, 2019)
This study aims to determine the development of students' independence in understanding the subject matter and efforts to improve student learning outcomes using the play method. This research is a type of classroom action research. The approach used is a qualitative approach. The subjects in this study were group A students of Pertiwi Pompanua Kindergarten, Bone District, odd semester 2018/2019 Academic Year, totaling 15 students. The object in this study is the application of outdoor and indoor learning strategies in improving student learning outcomes. The tool used to collect data is a test that is the initial test, test post I, test post II, interview and observation. This study consisted of two cycles. Efforts made to understand drawing material according to the wishes of students, researchers provide learning in groups. From giving actions to learning using the playing method in the first and second cycles, data were obtained about the average value and level of mastery of student learning. On the initial test, the average score of students was 1.93, at the time of the test post I the average score of students increased to 2.53 and at the time of the test post-II the average score of students increased to 3.33. While for completeness in the initial test only by 20%, the first cycle increased to 60%, even in the second cycle increased sharply to 86.67%. This means that the results obtained by students in the second cycle have reached the level of completeness in classics, namely ≥85% which reached a complete value of intang3 star. Furthermore, the attitude of students' independence, at the pre-cycle of 13.33, then in the first cycle increased to 53.33, and in the second cycle 86.67%. So it can be concluded that the use of playing methods can increase students' independence in understanding the subject matter and improving student learning outcomes.